Utility of quantitative measurement of T 2 using restriction spectrum imaging for detection of clinically significant prostate cancer - Mariluz Rojo Domingo; Christopher C. Conlin; Roshan Karunamuni; Courtney Ollison; Madison T. Baxter; Karoline Kallis; Deondre D. Do; Yuze Song; Joshua Kuperman; Ahmed S. Shabaik; Michael E. Hahn; Paul M. Murphy; et al. (Scientific Reports)
Abstract The Restriction Spectrum Imaging restriction score (RSIrs) has been shown to improve the accuracy for diagnosis of clinically significant prostate cancer (csPCa) compared to standard DWI. Both diffusion and T 2 properties of prostate tissue contribute to the signal measured in DWI, and studies have demonstrated that each may be valuable for distinguishing csPCa from benign tissue. The purpose of this retrospective study was to (1) determine whether prostate T 2 varies across RSI compartments and in the presence of csPCa, and (2) evaluate whether csPCa detection with RSIrs is improved by acquiring multiple scans at different TEs to measure compartmental T 2 (cT 2). Data includes two cohorts scanned for csPCa with 3T multi-b-value diffusion-weighted sequences acquired at multiple TEs. cT 2 values were computed from multi-TE RSI data and compared by compartment. CsPCa detection was compared between RSIrs and a logistic regression model (LRM) to predict the probability of csPCa using cT 2 in combination with RSI measurements. Two-sample t-tests (α = 0.05) and the area under the receiver operating characteristic curve (AUC) were used for the statistical analyses. In both cohorts, T 2 was different (p < 0.05) across the four RSI compartments (C 1, C 2, C 3, C 4 ). Voxel-level, cohort 1: T 2 was different in csPCa for C 1, C 2, C 3 (p < 0.001). Patient-level, cohort 1: T 2 was different in csPCa patients in C 3 (p = 0.02); cohort 2: T 2 differed in csPCa patients in C 1 (p = 0.01), C 3 (p = 0.01) and C 4 (p < 0.01). Voxel-level csPCa detection: cT 2 did not improve discrimination over RSIrs alone (p = 0.9). Patient-level: RSIrs and the LRM performed better than diffusion alone (p < 0.001), but the difference in AUCs between RSIrs and the LRM was not significantly different (p = 0.54). In conclusion, significant differences in cT 2 were observed between normal and cancerous prostatic tissue. With our data, however, consideration of cT 2 in addition to diffusion did not significantly improve cancer detection performance.